Bolezni, ki jih prenašajo klopi - Lotrič-Furlan, Stanka (Medicinski razgledi, 1996)
Ticks are well-known vectors of numerous diseases caused by bacteria, viruses and protozoa. In the recent years, the incidence of these illnesses has increased worldwide. Tick-borne meningoencephalitis and Lyme borreliosis are endemic in Slovenia. The authors review the latest findings in epidemiology, pathogenesis, clinical picture and treatment of tick-borne diseases, and stress their significiance and the risk of acquiring these diseases in Slovenia.
Keywords: klopi; bolezni; disease; zoonoze